If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 264 = 2(x + 26) Reorder the terms: 264 = 2(26 + x) 264 = (26 * 2 + x * 2) 264 = (52 + 2x) Solving 264 = 52 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 264 + -2x = 52 + 2x + -2x Combine like terms: 2x + -2x = 0 264 + -2x = 52 + 0 264 + -2x = 52 Add '-264' to each side of the equation. 264 + -264 + -2x = 52 + -264 Combine like terms: 264 + -264 = 0 0 + -2x = 52 + -264 -2x = 52 + -264 Combine like terms: 52 + -264 = -212 -2x = -212 Divide each side by '-2'. x = 106 Simplifying x = 106
| 6+2X-5=3+2 | | 2.1x+6-4.1x=10 | | =(2x+8)+(12x+6) | | 4(2x-1.7)=2x-6.8 | | 2x+8+12x+6 = (2x+8)+(12x+6) | | -2+2K-7-3=2 | | 1.6+0.2x=0.4 | | 3.5x-55=2.8x+8 | | 10=3+2A-10-5 | | 8.1=10x+3.3 | | 49a+7=7 | | 8x-67.2=x | | 5=-2+5+3Y-1 | | = 0+(9x-3x)+3 | | 4a-3+6a-7=180 | | 32-6x=y | | 9(x-4.4)=6.3 | | You=6x-32 | | u=v-at | | =m^2-10m-39 | | -3+4-C-2=6 | | 4(x+4)+2=8x+4(x+2) | | 11(2z+10)=264 | | 6x+9=6(x-8) | | 5(x+20)=50 | | 2x-6+4x+18=180 | | =N^2+8N+7 | | (x+14)(n-9)=0 | | x+11+x+x-13+104=360 | | 14=-1(2p-8) | | 25-25=20 | | -10=-2x-45 |